MARRIAGE CANCELLATION BECAUSE OF HUSBAND'S MISUNDERSTANDING ABOUT HIS WIFE (Decision Number: 700/Pdt.G/2020/PN.Mdn) - Sevania Abigael Naibaho; Mohamad Fajri Mekka Putra (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
This study aims to analyze the considerations of the State Court judges in annulling a marriage due to the husband's misunderstanding about his wife in Decision Number: 700/Pdt.G/2020/PN.Mdn and the legal implications of canceling a marriage due to the husband's misunderstanding about his wife. The research approach used is normative juridical law research or library research, with descriptive research type. The data analysis method used is qualitative. The results of this study indicate that the consideration of the District Court judge who granted the marriage annulment suit in the Medan District Court Decision Number: 700/ Pdt.G/2020/PN.Mdn was that the Petitioner wanted to marry the Respondent because among the Petitioners saw the quality of Education of the Respondent who claimed to be studying S1 and S2 at the University of Indonesia, and the profession of the Respondent who claims to work as a lawyer at the MAKES & Partners Law office. However, after the Petitioner married the Respondent, it turned out that the Respondent's confession did not match the truth, namely that the Respondent was proven to have studied S1 at Bung Karno University, and the Respondent had only worked at MNCTV for 1 (one) year. Because it has been proven that there has been a misunderstanding of the Petitioner against the Petitioner as described above, according to the Assembly, the Petitioner can prove the truth of the arguments of his application so that the Petitioner's application to annul his marriage is granted. The legal implication for the annulment of marriage due to a misunderstanding of the Petitioner (husband) against the Respondent (wife) is that the termination of the legal relationship between husband and wife results in the end of the household that has been formed, so that everything that was originally legal will become invalid after the court's decision. there is a court decision that grants the request for annulment of the marriage.